2008
DOI: 10.5009/gnl.2008.2.3.137
|View full text |Cite
|
Sign up to set email alerts
|

Precursor Lesions of Pancreatic Cancer

Abstract: This review article describes morphological aspects, gene abnormalities, and mucin expression profiles in precursor lesions such as pancreatic intraepithelial neoplasia (PanIN), intraductal papillary mucinous neoplasm (IPMN), and mucinous cystic neoplasm (MCN) of the pancreas, as well as their relation to pancreatic ductal adenocarcinoma (PDAC). The gene abnormalities in precursors of PDAC are summarized as follows: (1) KRAS mutation and p16/CDKN2A inactivation are early events whose frequencies increase with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 99 publications
3
70
0
Order By: Relevance
“…However, neither the myeloproliferative disease observed in Mx1-Cre;LSL-Kras G12D mice, nor the lung tumors seen in M-Cre;LSL-Kras G12D animals are genetically or histologically faithful to the analogous diseases seen in humans. In contrast, the neoplastic transformation and disease progression observed in the pancreas of Pdx1-Cre;LSL-Kras G12D mice faithfully mimics the progression of human pancreatic ductal adenocarcinoma (PDA) through a series of precursor lesions known as pancreatic intraepithelial neoplasias (PanINs) (11,12). Moreover, not only is PDA among the human cancers most frequently associated with oncogenic mutations in the KRAS gene (13), but activating mutations in the KRAS proto-oncogene have been found in patients with early PanIN lesions (14), suggesting that KRAS mutations may be an initiating genetic event for PDA.…”
Section: Introductionmentioning
confidence: 99%
“…However, neither the myeloproliferative disease observed in Mx1-Cre;LSL-Kras G12D mice, nor the lung tumors seen in M-Cre;LSL-Kras G12D animals are genetically or histologically faithful to the analogous diseases seen in humans. In contrast, the neoplastic transformation and disease progression observed in the pancreas of Pdx1-Cre;LSL-Kras G12D mice faithfully mimics the progression of human pancreatic ductal adenocarcinoma (PDA) through a series of precursor lesions known as pancreatic intraepithelial neoplasias (PanINs) (11,12). Moreover, not only is PDA among the human cancers most frequently associated with oncogenic mutations in the KRAS gene (13), but activating mutations in the KRAS proto-oncogene have been found in patients with early PanIN lesions (14), suggesting that KRAS mutations may be an initiating genetic event for PDA.…”
Section: Introductionmentioning
confidence: 99%
“…MUC6 was positive in 31.3% of dysplasias, and 18.2% in CC. Several authors demonstrated higher expression of these mucins in both CC and dysplastic epithelium, emphasizing that they are important in characterizing biliary and pancreatic pre-neoplastic lesions (7,11,15,20,21,24) . Although these results apparently substantiate the usefulness of mucins 5 and 6 in the characterization of preneoplastic lesions, we observed that both were also expressed in reactive epithelium in 40.3% and 11.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma (PDAC) is known as pancreatic cancer, is the most well-known exocrine-based pancreatic tumor. Scientific studies indicated that the progression of this malignancy is not solely dictated by the tumor cells themselves, but rather there is melodious synergy between tumor stromal cells with multiple signaling pathways [20].…”
Section: Epidemiology Of Pancreatic Cancermentioning
confidence: 99%